EULAR RECOMMENDATIONS FOR THE TREATMENT OF RHEUMATOID ARTHRITIS – 2013: GENERAL CHARACTERISTICS AND DISPUTABLE PROBLEMS - E. L. Nasonov; D. E. Karateev; N. V. Chichasova (Научно-практическая ревматология, 2015)
There has been significant progress in research focused on rheumatoid arthritis (RA) over the past decade. Nine innovative biologics agents – monoclonal antibodies and recombinant proteins inhibiting activity of the key proinflammatory cytokines and pathological activation of T and B cells involved in the development of the immune-inflammatory process – have been designed to treat RA. However, the radical improvement of prognosis in RA patients depends both on launching innovative drugs and refining the treatment strategy. This strategy is based on early diagnosis, which makes it possible to initiate the very early («window of opportunity drug») active and tightly controlled anti-inflammatory therapy aimed at achieving remission as soon as possible (the «Treat to Target» conception). The «Treat to Target» conception formulated by EULAR in 2010 has been widely incorporated in national guidelines on management of RA elaborated in many countries, including Russia. A new edition of EULAR recommendations was prepared in 2013; it has accumulated the scientific progress and clinical experience over the past three years. The publication is aimed at providing the general characteristics of the key provisions in the new recommendations and discussing some disputable problems that have not been solved yet and require further research.